Glycerol-triazole conjugated rhodamine as colorimetric and fluorimetric sensor for Cu2+ - Verma, Abhishek; Gahlyan, Parveen; Bawa, Rashim; Dash, Soumya Ranjan; Prasad, Ashok K.; Kumar, Rakesh (ChemistrySelect, 2021)
{A glycerol-triazole tethered rhodamine based colorimetric and fluorimetric sensor 3 `,6 `-bis(diethylamino)-2-(((1-(1,3-dihydroxypropan-2-yl)-1H-1,2,3-triazol-4 -yl)methylene)aminospiro [isoindoline-1,9 `-xanthen]-3-one (L1) is designed and synthesized for the selective recognition of Cu2+ ion. The sensor L1 allows naked eye detection of Cu2+ ion with a fast response (<1 min). Among the various metal ions tested, the sensor L1 shows selective binding with Cu2+ through turn-on fluorescence mechanism. The sensor shows 1 : 2 binding stoichiometry with binding constant
Keywords: Cu2+ Sensor; DFT; Glycerol; Rhodamine B; Triazole